A Legal Analysis Of Nterests Legal Protection For The Rights Of Victims Of Aggregated Theft - Dora Dame Madonna Nainggolan; T. Riza Zarzani; M. Hary Angga Pratama Sinaga (Sean Institute, 2024)
Legal protection is any form of effort to protect human dignity and honor and recognition of Human Rights (HAM) in the legal field. Legal protection as a victim of a crime, especially theft, even with aggravation, the victim has the right to receive legal protection, in providing this legal protection must be maximized, especially victims who are economically weak. In decision No. 1743 / Pid.B / 2023 / PN Lbp, the defendant committed a crime of aggravated theft by stealing an RX King motorbike belonging to the victim and a witness, in this case the victim suffered material and immaterial losses due to the loss of the motorbike, but the judge only focused on determining the sanctions and the final sentence that would be imposed on the defendant and rarely discussed the rights of victims who were victims of the crime of aggravated theft and returned their rights in the final decision. In this study, the researcher formulated the problems to be discussed, namely: What are the general provisions related to the crime of aggravated theft, How is the legal review of the form of legal protection for losses to victims of criminal acts and How is the author's legal analysis of the interests of legal protection for the rights of victims of losses due to the crime of aggravated theft in the study of decision No. 1743 / Pid.B / 2023 / PN Lbp. This study uses a normative study method which is descriptive analytical research that provides an overview of the object being studied with a research method that focuses on collecting and analyzing data to understand and explain certain systems, processes, or phenomena. As a result of the study, the author found that in protecting the rights of victims of criminal acts or those related to criminal acts, the law in Indonesia regulates very strictly which has been regulated in Law No. 13 of 2006 concerning the protection of victims and witnesses in Article 281 paragraph 4, victims should be able to file for legal restitution. Victims can also apply for their rights to be protected by LPSK (Witness and Victim Protection Agency).